Maths-
General
Easy

Question

Ray OQ bisects βˆ π‘ƒπ‘‚π‘….Β Find the value of x.

hintHint:

  • The angle whose measure is 90oΒ is called a right angle.
  • Measure of straight angle is 180o.

The correct answer is: 11


    • Step by step explanation:Β 
      • Given:

    π‘šβˆ POQ = (x - 4) °  

    π‘šβˆ QOR = (5x - 20) Β°.

    • Step 1:
    • From the figure it is clear that,

    ∠POR is right angle hence ∠POR = 90o.
    andΒ 

    ∠POR = ∠POQ + ∠QOR 

    • Step 2:
    • Put values of ∠COD and ∠COPΒ 

    ∠POR = ∠POQ + ∠QOR  

    90 = (x - 4) +Β (5x - 20)

    90 = 5x + x - (20 + 4)

    90 = 6x -Β 24

    6x = 90 - 24

    6x = 66

    x =Β 66 over 6

    x = Β 11

    • Final Answer:
    Hence, the x is 11.

    Related Questions to study

    General
    Maths-

    Identify all pairs of congruent angles and congruent segments.

    Identify all pairs of congruent angles and congruent segments.

    Maths-General
    General
    Maths-

    ∠𝐴 &β€ˆβˆ π΅ are complementary.  ∠𝐡 &β€ˆβˆ πΆ are complementary. Prove: ∠𝐴 β‰… β€ˆβˆ πΆ

    ∠𝐴 &β€ˆβˆ π΅ are complementary.  ∠𝐡 &β€ˆβˆ πΆ are complementary. Prove: ∠𝐴 β‰… β€ˆβˆ πΆ

    Maths-General
    General
    Maths-

    Given: Ray OR bisects βˆ π‘ƒπ‘‚π‘†.
    Prove: π‘šβˆ 1 = π‘šβˆ 2

    Given: Ray OR bisects βˆ π‘ƒπ‘‚π‘†.
    Prove: π‘šβˆ 1 = π‘šβˆ 2

    Maths-General
    parallel
    General
    Maths-

    Solve the following by using the method of substitution
    Y = - 2X-3
    Y = - X-4

    Solve the following by using the method of substitution
    Y = - 2X-3
    Y = - X-4

    Maths-General
    General
    Maths-

    Solve the system of equations by elimination :
    X - 2Y = 1
    2X + 3Y= - 12

    Solve the system of equations by elimination :
    X - 2Y = 1
    2X + 3Y= - 12

    Maths-General
    General
    Maths-

    Solve the equation. Write a reason for each step.
    π‘₯ βˆ’ 2 + 3(π‘₯ + 2) = 3π‘₯ + 10

    Solve the equation. Write a reason for each step.
    π‘₯ βˆ’ 2 + 3(π‘₯ + 2) = 3π‘₯ + 10

    Maths-General
    parallel
    General
    Maths-

    Use Substitution to solve each system of equations :
    6X - 3Y = -6
    Y = 2X + 2

    Use Substitution to solve each system of equations :
    6X - 3Y = -6
    Y = 2X + 2

    Maths-General
    General
    Maths-

    Given: π‘šβˆ π‘ƒ = 30Β°, π‘šβˆ π‘„ = 30Β° , π‘šβˆ π‘„ = π‘šβˆ π‘…
    Prove: π‘šβˆ π‘ƒ β‰… π‘šβˆ π‘… = 30Β°

    Given: π‘šβˆ π‘ƒ = 30Β°, π‘šβˆ π‘„ = 30Β° , π‘šβˆ π‘„ = π‘šβˆ π‘…
    Prove: π‘šβˆ π‘ƒ β‰… π‘šβˆ π‘… = 30Β°

    Maths-General
    General
    Maths-

    Use the given information and the diagram to prove the statement.
    Given: π‘šβˆ π‘ƒπ‘€πΆ + π‘šβˆ π‘ƒπ‘€π· = 180Β° and π‘šβˆ π‘ƒπ‘€πΆ = 150Β°
    Prove: π‘šβˆ π‘ƒπ‘€π· = 30Β°

    Use the given information and the diagram to prove the statement.
    Given: π‘šβˆ π‘ƒπ‘€πΆ + π‘šβˆ π‘ƒπ‘€π· = 180Β° and π‘šβˆ π‘ƒπ‘€πΆ = 150Β°
    Prove: π‘šβˆ π‘ƒπ‘€π· = 30Β°

    Maths-General
    parallel
    General
    Maths-

    Solve the system of equations by elimination :
    3X + 2Y = 8
    X + 4Y = - 4

    Solve the system of equations by elimination :
    3X + 2Y = 8
    X + 4Y = - 4

    Maths-General
    General
    Maths-

    Give a two-column proof.
    Given:

    Prove: PR = 25 in

    Give a two-column proof.
    Given:

    Prove: PR = 25 in

    Maths-General
    General
    Maths-

    Use Substitution to solve each system of equations :
    - 3X - Y = 7
    X + 2Y = 6

    Use Substitution to solve each system of equations :
    - 3X - Y = 7
    X + 2Y = 6

    Maths-General
    parallel
    General
    Maths-

    If Q is the midpoint of PR, prove that PR = 2 PQ.
    Give a two-column proof.

    If Q is the midpoint of PR, prove that PR = 2 PQ.
    Give a two-column proof.

    Maths-General
    General
    Maths-

    Compare π‘šβˆ π‘ƒπ‘‚π‘„π‘Žπ‘›π‘‘βˆ π‘†π‘‚π‘‡.

    Compare π‘šβˆ π‘ƒπ‘‚π‘„π‘Žπ‘›π‘‘βˆ π‘†π‘‚π‘‡.

    Maths-General
    General
    Maths-

    Which postulate will you use to prove that PR = PQ + QR?

    Which postulate will you use to prove that PR = PQ + QR?

    Maths-General
    parallel

    card img

    With Turito Academy.

    card img

    With Turito Foundation.

    card img

    Get an Expert Advice From Turito.

    Turito Academy

    card img

    With Turito Academy.

    Test Prep

    card img

    With Turito Foundation.